PERBANDINGAN EKSTRAKSI JAMUR TIRAM (Pleurotus ostreatus) DAN JAMUR KANCING (Agaricus bisporus) - Christa Marthaningsih Prisida; Christe Mareta Ardika Sari; Tarasia Gandes Belani; Lusia Murtisiwi (Jurnal Insan Farmasi Indonesia, 2019)
Mushrooms contain polysaccharides with the main components namely Î²-glucan and Î±-mannan. Polysaccharides can be useful as immune enhancers because beta-glucans can increase phagocytic activity and cytokine production. Î²- (1,3) -glukan has the ability to activate the cellular and humoral immunity system which is a component of the body's immune system. Î²- (1,3) -glukan increases the antimicrobial activity of mononuclear and neutrophil cells and increases the functional activity of macrophages. Polysaccharides from oyster mushrooms and button mushrooms can be extracted using the Yap & Ng method. The purpose of this study was to compare the yield of extracts produced from oyster mushrooms and button mushrooms. The method used in this research is water extraction method based on Yap & Ng. Data analysis of this study was carried out by calculating the percentage of extracts of oyster mushrooms and button mushrooms, then compared. The results of this study indicate that the yield of oyster mushroom extract is0,013% while the yield of button mushroom extract is 0,0055%. This shows the yield of oyster mushroom extract is greater than the yield of button mushroom extract if extracted by the Yap & Ng method.